Description of the pupae of Lepidophora culiciformis Walker, 1850 (Diptera, Bombyliidae, Ecliminae) and host records - Lamas, Carlos José Einicker; Lopes, Daniele De Araujo (Zootaxa, 2004)
The pupae of Lepidophora culiciformis Walker, 1850 is described and illustrated. Three species of Sphecidae (Hymenoptera) are recorded as hosts of the immature stages of L. culiciformis. The geographical range of the species is also enlarged.